KONSEPSI PANCA DHARMA KI HADJAR DEWANTARA DITINJAU DARI SUDUT PANDANG PENDIDIKAN ISLAM - Solehan Solehan (Ta'dib: Jurnal Pendidikan Islam, 2010)
Panca Dharma is important education concept of Ki Hajar Dewantara. It contains five of main ideas on education, i.e.: natural base, freedom base, living base, cultural base, nation base, and humanity base. The five bases of education, in reality, had been implemented in daily live of Yayasan Pendidikan Taman Siswa, Ki Hajar’s education foundation. If five of bases are viewed from Islamic education concept they are relevant in the mean that five bases are also considered as foundation principles of Islamic education. Meanwhile, there are some differences between of two, such as from terminology and referencese that is used.